Preliminary study on porphyrin derivatives as transfection reagents for mammalian cell - Khorami, Hajar Hossein (2013)
Porphyrins are organic, aromatic compounds found in heme, cytochrome, cobalamin, chlorophyll and many other natural products with essential roles in biological processes that their cationic forms has been used as a groups of favorable non-viral vectors recently. Cationic porphyrins are self-chromogenic reagents with high capacity for modifications, great interaction with DNA and protection of DNA from nuclease during delivery of it into cell with low toxicity. In order to have high efficient gene transfection into cell while causing low toxicity, genetically manipulations of nonviral vector, cationic porphyrin, would be useful. In this study newly modified cationic porphyrins namely, 5-hexyl-10,15,20tris (N-methyl-4-pyridyl) porphyrin, 5-propyl- 10,15,20tris (N-methyl-4-pyridyl) porphyrin, 5,10-dipropyl-15,20-bis (N-methyl-4- pyridyl) porphyrin, 5,10-dihexyl-15,20bis (N-methyl-4-pyridyl) porphyrin, and polyamidoamine (PAMAM) G4-porphyrin conjugate were applied. Cytotoxicity of synthesize cationic porphyrins on Chinese Hamster Ovarian (CHO) cells, were evaluated by using MTT assay. Generally, all cationic derivatives are dose dependent, with low cytotoxicity at the ranges from 100 µM to 0.01µM. Four of cationic porphyrin were uptake by cell at high concentration while none were observed on conjugate one. Using different concentration of cationic porphyrins and methods were tested on transfection of CHO cells by using the derived transfection reagent with X-tremeGENE HP DNA as positive control. However no transfection observed by all the porphyrin derivat ives and the parameters tested except for positive control. Results of this study suggested that applying different protocol, and also trying other concentration of cationic porphyrins and DNA for forming a strong complex would increase the possibility of efficient gene transfection by using cationic porphyrins.